Effect of Using Venturi-type Bubble Generator with Pressure Tank on Micro Bubble Generation for Aeration - Panich, Parinya; Tawonsri, Prapaipis; Nuntadusit, Chayut (Princess of Naradhiwas University Journal, 2021)
Usage of air diffuser or jet aerator was a typical technique that used for oxygenation process. However, the occurred bubbles were unstable, rapidly floated to the water surface and small amount of dissolved oxygen level. The objective of this study was to increase the efficiency of air bubble generator to produce the microbubble applying the venturi principle and pressure. Venturi-type microbubble generator at various pressure (1, 2, 3, 4, 5 and 6 kg/cm2) and air diffuser were studied and compared. It was found that, the air bubbles from venturi-type microbubble generator without pressure and air diffuser were larger than 1 mm. Because of the unstable bubbles, the water only contained dissolved oxygen level at 3.72 mg/l. Whereas, the size of bubbles was decrease with increasing the pressure level. Venturi-type microbubble generator with pressure at 6 kg/cm2 generated the microbubble size 46.13 µm, the water contained dissolved oxygen level at 7.40 mg/l which had the highest rate of dissolved oxygen level. Moreover, venturi-type microbubble generator with pressure at 6 kg/cm2 also had the highest in the oxygen transfer coefficient, oxygenation capacity, oxygen transfer rate and aerator efficiency which were 6.01 hr-1, 33.20x10-4 mg O2/hr, 3.70 mg O2/kW/hr and 6.90%, respectively.